Performance Evaluation Using the Discrete Choquet Integral: Higher Education Sector - Seher Nur Sülkü; Deniz Koçak (International Journal of Assessment Tools in Education)
Performance evaluation functions as an essential tool for decisionmakers in the field of measuring and assessing the performance under themultiple evaluation criteria aspect of the systems such as management, economy,and education system. Besides, academic performance evaluation is one of thecritical issues in higher institution of learning. Even though the academicevaluation criteria are inherently dependent, most of the traditionalevaluation methods take no account of the dependency. Currently, the discreteChoquet integral can be proposed as a useful and effective aggregation operatordue to being capable of considering the interactions among the evaluationcriteria. In this paper, it is aimed to solve an academic performanceevaluation problem of students in a university in Turkey using the discreteChoquet integral with the complexity-based method and the entropy-based method.Moreover, the k-means method, whichhas been widely used for evaluating students’ performance over 50 years, isused to compare the effectiveness and the success of two different frameworksbased on discrete Choquet integral in the robustness check. Our resultsindicate that the entropy-based Choquet integral outperforms thecomplexity-based Choquet and k-meansmethod in most of the cases.